A 'School' Person in a 'Red' Blanket: The Case of SEK Mqhayi. Issue 1 (2nd January 2021) - Chapman, Michael
Abstract : The article considers the scope and purpose of the project, "Translating (South) African Literatures", in relation to the early twentieth-century Xhosa writer, SEK Mqhayi, two of whose works have been translated into English in the project. Turning to the several prompts to reflection offered by the project, I evaluate Mqhayi's contribution to an 'expanded' South African literary history. As does the project, my argument requires a return to the archive, in this case of Mqhayi's dual commitment to both Xhosa custom ('Red') and colonial-Christian modernisation ('School'). A brief comparison of Mqhayi's plain voice of ethical justice and, in the mid-1920s, the experimental modernism of his contemporary, William Plomer, raises the issue of an appropriate aesthetic in an expanded literary history, while I conclude with a key consideration in any translation project: the need for a 'usable' theory and practice of translation.